INTERNATIONAL TRIBUNALS AS A MECHANISM FOR COMBATING CRIMES IN THE RUSSIAN-UKRAINIAN WAR - Olkhovik, Myroslava; Yakymenko, Pavlo; Senchenko, Andrii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to reveal the legal precedent of international tribunals in relation to war crimes as a component of the legal mechanism for bringing perpetrators to justice in the future international tribunal for war crimes of the Russian Federation. Research methods: to achieve the study’s objectives, a range of research methods were employed. These include the formal and logical method, system analysis, and the structural and functional method. Results: the research findings shed light on the legal and historical practices employed by international tribunals in addressing war crimes. By examining the prosecution and punishment of war crime perpetrators, the study identifies pertinent precedents that can inform the future international tribunal on war crimes of the Russian Federation. Discussion: the discussion section focuses on the expediency and appropriateness of incorporating international tribunal precedents into the framework of the future international tribunal on war crimes of the Russian Federation. The identified precedents serve as a valuable guide for formulating effective legal strategies and ensuring a fair and impartial judicial process. Conclusion: based on the analysis of international tribunal precedents, this study highlights their importance in shaping the legal mechanisms of the forthcoming international tribunal on war crimes of the Russian Federation. By drawing from the experiences of previous tribunals, it is possible to establish a robust framework that upholds the principles of justice, accountability, and deterrence.